FUNDAMENTAL ASPECTS OF THE COMPANY IN INCREASING DIVIDENDS - Saptian, Egi; Safitri, Rika Henda; Mukhtaruddin, Mukhtaruddin (Faculty of Economics and Business, 2025)
This study aims to examine the influence of debt policy, free cash flow, profitability, liquidity, and firm size on dividend policy in mining companies listed on the Indonesia Stock Exchange for the period 2019–2023. The sampling method used is purposive sampling with a total of 75 companies. The data processing technique employed is multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 25. The test results in this study indicate that free cash flow has a positive and significant influence on dividend policy, while debt policy, liquidity, and firm size do not have a significant effect on dividend policy. Meanwhile, profitability has a negative and significant effect on dividend policy.